THE ROLE OF PSYCHOVEGETATIVE DYSFUNCTIONS IN THE PATHOGENESIS OF THE PRURIGO - K.M. MUKHAMADIEVA; S.S. ISMATULLOEVA; AL-MAAMARI AHMED MUHIDDIN ABDURUB (Avicenna Tajik State Medical University, 2017)
The article presents an analysis of the current and most significant publications devoted to the study of the role of psychovegetative disorders in the pathogenesis of prurigo. Based on generalized literature data, the authors focus on the relationship between prurigo and disorders of the nervous system. It is noted, that the starting mechanism of complex changes in the central nervous system can be a variety of external irritants such as negative emotions and mental trauma.